MINERALOGY OF APATITE-AEGIRINE-MESOPERTHITE PEGMATITES OF MINE NO. 243 OF THE ILMENY STATE RESERVE (SOUTH URALS) - E.P. Makagonov; S.А. Repina; M.A. Rassomakhin (Минералогия, 2023)
The paper describes mineralogy of apatite-aegirine-mesoperthite pegmatites, which are located in a fenite halo at the southeastern contact of the Selyankino syenite block (Ilmeny State Reserve, South Urals). Two pegmatite veins are exposed by mines. The pegmatites differ from the known veins of the Ilmeny State Reserve in a high amount of apatite and the presence of the best collection aegirine druses. The pegmatites contain albite, microcline, aegirine, hydroxyapatite, fluorapatite, calcite, titanite, chevkinite-(Ce), magnetite, ilmenite, hematite, rutile, Fe and Mn hydroxides, monazite-(Ce), rhabdophane-(Ce), rhabdophane-(La), and dalnegorskite.